Rol de la Avifauna en artes del espectáculo de la parroquia de Zumbahua - Jami Quinga, Danny Mauricio (2021)
The objective of this research was to study the role of the local avifauna in the performing arts of the parish of Zumbahua and, based on the data collected, to design an informative guide to promote the recovery and conservation of the cultural heritage of the sector. The study began with the theoretical foundation by compiling bibliographic and documentary information. Subsequently, a field investigation was carried out using the ethnographic method and using the files of the National Institute of Cultural Heritage as an instrument. The interview and the collective memory and snowball methods were also used as techniques.A socioeconomic diagnosis of Zumbahua was carried out with a total population of 12,643 inhabitants, most of which are registered as indigenous in the INFOPLAN 2015 reports. Of the total population, 6,440 are women, 5,455 men. Regarding its main economy, it is presented that 72.56% are engaged in agricultural, livestock and agricultural activities, their main economic income coexisting, 11.62% in industry and construction for economic stability, 15.82% of the economy of the parish are service, production process, trade, tourism, culture, shows between enterprises in the area in the bird inventory, from the field research two birds present in the performing arts were identified, the Andean condor and the carunculated or curiquinguecaracará. The arts in which they intervene are, in the case of the condor, in the legend and play "The condor in love" a symbol of spirituality and power, being the largest bird and considered the king of the Andes, in addition to being represented in the national symbol of Ecuador. “Called 'ApuKurtur”, and in the case of the curiquingue, in the music and dance “faces-faces curiquingue”, also locally called Curiquingue, a bird of the Andean moor considered mystical and as a sign of good luck in the crops of the communities.Finally, a descriptive guide to the birdlife in the performing arts of the Zumbahua parish was designed to strengthen and protect the established cultural heritage.